2010
DOI: 10.1128/jb.00141-10
|View full text |Cite|
|
Sign up to set email alerts
|

Membrane Topology and Identification of Critical Amino Acid Residues in the Wzx O-Antigen Translocase from Escherichia coli O157:H4

Abstract: Wzx belongs to a family of membrane proteins involved in the translocation of isoprenoid lipid-linked glycans, which is loosely related to members of the major facilitator superfamily. Despite Wzx homologs performing a conserved function, it has been difficult to pinpoint specific motifs of functional significance in their amino acid sequences. Here, we elucidate the topology of the Escherichia coli O157 Wzx (Wzx EcO157 ) by a combination of bioinformatics and substituted cysteine scanning mutagenesis, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…In this study, we also found that Wzx C1 shared limited deduced amino acid sequence identity with other Wzx flippases (BLASTp), however, the topological prediction algorithms revealed very high similarity between the Wzx C1 and Wzx from S. Typhimurium and E. coli O157:H7 (Fig. S1), whose topological profiles have been reported based on experimental data [21], [22]. It has been reported that O-antigen construction in S. Choleraesuis is made of repeating units of the identical mannose sugar (i.e., homopolymeric O antigens), while the O-antigen of S. Typhimurium or E. coli O157:H7 are heteropolymeric, being composed of various sugars such as mannose, rhamnose and galactose [13].…”
Section: Discussionsupporting
confidence: 74%
“…In this study, we also found that Wzx C1 shared limited deduced amino acid sequence identity with other Wzx flippases (BLASTp), however, the topological prediction algorithms revealed very high similarity between the Wzx C1 and Wzx from S. Typhimurium and E. coli O157:H7 (Fig. S1), whose topological profiles have been reported based on experimental data [21], [22]. It has been reported that O-antigen construction in S. Choleraesuis is made of repeating units of the identical mannose sugar (i.e., homopolymeric O antigens), while the O-antigen of S. Typhimurium or E. coli O157:H7 are heteropolymeric, being composed of various sugars such as mannose, rhamnose and galactose [13].…”
Section: Discussionsupporting
confidence: 74%
“…We used two complementary approaches to determine the topology of MurJ experimentally: reporter fusion technology and the substituted cysteine accessibility method (SCAM). Similar approaches have been used for the MOP exporter and O-antigen flippase Wzx (38,62,63). For the reporter strategy, we employed a dual-reporter fusion system (39).…”
Section: Resultsmentioning
confidence: 99%
“…Soluble or membranebound GTs complete the repeating-unit structure in a sequential manner. The repeating units are then flipped to the periplasmic side of the inner membrane or across the cytoplasmic membrane by a Wzx flippase (109). The Wzy polymerase builds up the CPS/ EPS structure by the assembly of several repeating units at the reducing end of the growing polymer (61).…”
Section: Cell Wall Polysaccharides: Capsular Polysaccharides and Exopmentioning
confidence: 99%